1989
DOI: 10.1099/0022-1317-70-5-1065
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequences of the Coat Protein Genes and Flanking Regions of Cucumber Mosaic Virus Strains C and WL RNA 3

Abstract: SUMMARYSeveral strains of cucumber mosaic virus (CMV) have been classified, and nucleic acid hybridization data indicate that these strains differ widely in nucleotide sequence. We have constructed cDN A clones of the coat protein coding regions of CMV strains C and WL, and have compared the nucleotide sequences of the RNA 3 intergenic region, coat protein gene, and 3' untranslated region with published CMV sequences from the same regions of the Q, D and Y strains. These comparisons show that the C and WL stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Isolates in MspI restriction group I produced a single D N A product and isolates in restriction group 2 produced the same product and an additional minor product. It is worth noting that the possible priming sites Q 248, 197, 158, 126, 110, 28 S Davies & Symons (1988) WL 248, 197, 158, 126, I10, 28 S Quemada et al (1989 MspI group 1 This work CP91/454 248, 197, 158, 126, 110, Comparison of the c D N A sequences from some of our isolates with those published for six other CMV isolates (Davies & Symons, 1988;Quemada et al, 1989;Hayakawa et al, 1989;Owen et al, 1990) confirmed that only our two MspI restriction patterns were present. Furthermore our restriction groups divided the six other CMV isolates into their previously established subgroups (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates in MspI restriction group I produced a single D N A product and isolates in restriction group 2 produced the same product and an additional minor product. It is worth noting that the possible priming sites Q 248, 197, 158, 126, 110, 28 S Davies & Symons (1988) WL 248, 197, 158, 126, I10, 28 S Quemada et al (1989 MspI group 1 This work CP91/454 248, 197, 158, 126, 110, Comparison of the c D N A sequences from some of our isolates with those published for six other CMV isolates (Davies & Symons, 1988;Quemada et al, 1989;Hayakawa et al, 1989;Owen et al, 1990) confirmed that only our two MspI restriction patterns were present. Furthermore our restriction groups divided the six other CMV isolates into their previously established subgroups (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While coat protein is required for encapsidation of the genomic RNAs into virus particles, important in aphid transmission [7,30] and affecting symptom expression [42,49]. CMV strains are divided into two subgroups I and II [3,31,33] and subgroup I is subdivided into IA and IB based on nucleotide sequence of the 3 0 untranslated region of RNA3 [37]. Nucleotide sequence similarity among IA and IB subgroup strains is 92-94 %.…”
Section: Introductionmentioning
confidence: 99%
“…The putative coat protein amino acid sequences of these strains were compared with those of other chlorosis-inducing (M-and Y-CMV) as well as mosaic-inducing (Fny-, O-, D-and C-CMV) strains (Owen et al, 1990;Hayakawa et al, 1988Hayakawa et al, , 1989Cuozzo et al, 1988;Quemada et al, 1989).…”
mentioning
confidence: 99%